Orienteering Sports Development Survey in Bengkulu City - Respi Candra Pratama; Citra Dewi; Supriyanto Supriyanto (Penerbit Jurnal Indonesia, 2022)
Sports from various branches around the world have undergone many developments from the beginning of humans knowing sports to modern times like today. In the development of sports in this world, many new types of sports have emerged, and orienteering is no exception. This study aims to: Find out how far this orienteering sport has developed in Bengkulu City from 2019 until now. This study uses qualitative methods, namely observation, interviews, or document review. The informants of this research are individual administrators whose function is to provide information. The data analysis technique of this research is the process of searching for data and systematically compiling the data obtained. FONI in Bengkulu province has been officially established and already has a board. The development of orienteering in Bengkulu is still developing and not many people know about this sport. Orienteering in Bengkulu itself does not yet have the facilities and infrastructure to support the future activities.